Land configurations and phosphorus management for improved productivity, economics and resource-use efficiency of soybean in Kandahar province of Afghanistan - HAQMAL, MOHIBULLAH; DASS, ANCHAL; NASRAT, NASIR AHMAD; CHOUDHARY, ANIL K.; SUDHISHRI, S.; KUMARI, KAVITA; SAN, AYE AYE; SARKAR, SUSHEEL K. (Journal of Soil and Water Conservation, 2024)
Cultivation of soybean (Glycine max L.) is being promoted in Afghanistan but its productivity is low due to various biotic and abiotic stresses. The current field investigation was conducted at Afghanistan National Agriculture Science & Technology University (ANASTU), during the summer season of 2020 to determine the suitable land configuration and phosphorus rate for enhancing the productivity of soybean in Kandahar region of Afghanistan. The experiment was conducted in a split-plot design and there were 16-treatment combinations viz., 4-land configurations (flat beds (FB), narrow beds with irrigation in all furrows (NBIF), narrow beds with irrigation in alternate furrows (NBIAF), broad beds (BB)) in main-plots and 4-Phosphorous rates (control (0), 30, 60 and 90 kg P2O5 ha-1) in sub-plots. Land configuration BB resulted in significantly higher dry matter accumulation over NBIAF and NBIF. Moreover, BB resulted in 32.9 and 18.8% higher grain yield than FB and NBIAF, and 150, 58.5 and 20.4% higher water productivity compared to FB, NBIF and NBIAF, respectively. However, significantly higher values of gross return and net return were recorded with NBIF. Again, the NBIF resulted in the highest production efficiency (16.7 kg ha-1 day-1), while agronomic efficiency and partial factor productivity were the highest under FB. Among the P-rates, increasing rates of P-application from 0 to 90 kg P2O5 ha- 1 though caused increase in dry matter accumulation, grain yield, and improved water productivity and production efficiency, but the increase was significant upto 60 P2O5 ha-1. However, the net return increased significantly upto 90 kg P2O5 ha-1; the per cent increase in net return due to 30, 60 and 90 kg P2O5 ha-1 was 2.5, 16.5 and 21.8% over control, respectively. Thus, cultivation of soybean on broad bed with 60 kg P2O5 ha-1 was more productive and economical for Kandhar region of Afghanistan.